ANALISIS TINGKAT PENDIDIKAN DAN LITERASI KEUANGAN PADA PETUGAS PARKIR DI KOTA PONTIANAK - Marianus Ronaldo Jubata Mare; Herkulana Herkulana; Achmadi Achmadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to determine the level of education and financial literacy of parking attendants in the city of Pontianak. The research method used is descriptive in the form of survey research. The approach taken by the researcher is a qualitative approach. The indicators in this study are education level, financial knowledge, savings and insurance carried out in five traditional markets in the city of Pontianak, namely: 1. Flamboyant market, 2. mawar market, 3. kemuning market, 4. Dahlia market, and 5. Parit besar market. big. Based on the results of the research conducted, it shows that in the last education level, Senior high school 5 people, junior high school 3 people, and primary school 6 people, the financial knowledge of parking officers almost all parking officers do not understand financial knowledge, savings shows that some of the 14 parking attendants who set aside the income for saving is 7 people and those who don't save are 7 people, insurance shows that parking attendants who have insurance are 2 people and those who don't have insurance are 12 people, So, the education level and financial literacy of 14 parking attendants are supported by 26 books, 13 journals and 8 previous thesis.Keywords: Education Level, Financial Literacy, Parking Officer.